Sex Differences in Presentation but Not in Outcome for ACTH-Dependent Cushing's Syndrome - Broersen, Leonie H. A.; van Haalen, Femke M.; Kienitz, Tina; Biermasz, Nienke R.; Strasburger, Cristian J.; Dekkers, Olaf M.; Pereira, Alberto M. (Frontiers in Endocrinology, 2019)
Background: Sex differences in clinical picture of ACTH-dependent Cushing’s syndrome are controversial, except for the known higher prevalence in females. We compared a broad range of potential differences to enable a more accurate understanding of the clinical picture of sex-specific ACTH-dependent Cushing’s syndrome. Methods: Cohort study including consecutive patients with ACTH-dependent Cushing’s syndrome from Leiden and Berlin diagnosed between 2000-2016. We compared clinical presentation, biochemical parameters, diagnostic tests, surgical outcome, and comorbidities between men and women. Results: We included 130 patients: 37 males and 93 females. With similar cortisol concentrations, ACTH concentrations were higher in males than females at time of diagnosis (median: 116 ng/L versus 57 ng/L). The prevalence of osteoporosis was higher in males than in females (48.6% versus 25.0%), persisting after surgery, with more vertebral fractures (16.2% versus 5.4%) before surgery. Males showed more anemia (75.9% versus 36.8%) after surgery. There were no differences in etiology, pituitary tumor size, diagnostic and therapeutic strategy, or surgical outcome between sexes. Conclusions: Based on this study, males and females with ACTH-dependent Cushing’s syndrome present different clinical patterns. However, these differences do not justify different diagnostic strategies or treatment based on sex, considering the similar surgical outcome. Clinicians should be alert to diagnose accompanying osteoporosis (with fractures) in male patients with ACTH-dependent Cushing’s syndrome.